SARS‐CoV‐2 infection in persons living with HIV: A single center prospective cohort. Issue 2 (8th October 2020) - Maggiolo, Franco; Zoboli, Fabio; Arosio, Marco; Valenti, Daniela; Guarneri, Davide; Sangiorgio, Lorena; Ripamonti, Diego; Callegaro, Annapaola
Abstract: Information about severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection in HIV‐infected individuals is scarce. In this prospective study, we included HIV (human immunodefeciency virus)‐infected individuals (people living with HIV [PLWHIV]) with confirmed SARS‐CoV‐2 infection and compared them with PLWHIV negative for SARS‐CoV‐2. We compared 55 cases of SARS‐CoV‐2 infection with 69 asymptomatic PLWHIV negative for SARS‐CoV‐2 reverse transcription‐polymerase chain reaction and/or serology. There was no significant difference between SARS‐CoV‐2 positive or negative patients for age distribution, gender, time with HIV infection, nadir CD4‐cell counts, type and number of co‐morbidities, current CD4 and CD8 counts and type of anti‐HIV therapy. Positive patients presented with a median of three symptoms (interquartile range, 1‐3). Most common symptoms were fever (76%), dyspnea (35%), anosmia (29%) non‐productive cough (27%), fatigue 22%), and ageusia (20%). Ten patients (18%) were completely asymptomatic. Four (7.2%) subjects died of coronavirus disease 2019. Factors significantly ( P < .05) associated with death included age and number of co‐morbidities, while time from HIV infection and lower current CD4 counts were significant only in univariate analysis. HIV‐infected individuals are not protected from SARS‐CoV‐2 infection or have a lower risk of severe disease. Indeed, those with low CD4 cell counts might have worse outcomes. Infection is asymptomatic in a large proportion of subjects and this is relevant for epidemiological studies. Highlights: This study addresses the question if specific characteristics of HIV infection may raise the risk of SARS‐CoV‐2 infection by comparing infected persons living with HIV (PLWHIV), either symptomatic or not, with other PLWHIV who tested negative for SARS‐CoV‐2 infection. None of the parameters classically used to define immune suppression or risk of immune impairment in HIV positive subjects does correlate with the risk of acquiring SARS‐CoV‐2 infection. Although low CD4 counts were not associated with the positivity for SARS‐CoV‐2, relative immunosuppression did seem to affect disease severity, and it might be associated with adverse outcomes. By contrast, there was no evidence that any specific antiretroviral drug affected SARS‐CoV‐2 infection or COVID‐19 severity. The disease may cover a vast range of clinical pictures, being almost one fifth of infected individuals asymptomatic and variables already described for the general population as risk factors for a more severe disease such as advanced age and the presence of multiple co‐morbidities do apply to PLWHIV, too. HIV‐infected individuals should not be considered protected from SARS‐CoV‐2 infection or as having lower risk of severe disease. Indeed, those with low CD4 cell counts might have worse outcomes than individuals with restored immunity. Infection may be asymptomatic in a large proportion of subjects and this variable must be counted when epidemiological studies are implemented in PLWHIV.